Long-Lasting Effects of Socialist Education - Nicola Fuchs-Schündeln; Paolo Masella (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Political regimes influence the contents of education and the criteria used to select and evaluate students. We study the impact of a socialist education on the likelihood of obtaining a college degree, as well as on several labor market outcomes, by exploiting the reorganization of the school system in East Germany after reunification. Our identification strategy exploits cut-off birth dates for school enrollment that lead to variation in the length of exposure to the socialist education system within the same birth cohort. We find that an additional year of socialist education substantially decreases the probability of obtaining a college degree, and also affects longer-term labor market outcomes for males. The effects likely stem from non-meritocratic restrictions in access to high school and college, central planning of vocational training, and curricula directed towards the transmission of socialist values in school.
Keywords: I20; J24; P36; 330